Effect of Supplemental Multi-Enzymes in the Diet of Meat-Type Ducks on Production Performance, Carcass Yields and Gastrointestinal Morphology - Puangkhum, Chudapun; Rakangthong, Choawit; Poeikhampha, Theerawit; Poungpong, Kanokporn; Bunchasak , Chaiyapoom (International Journal of Poultry Science, 2019)
Objective: The effect of mixed enzymes supplementation in the diet of meat-type ducks were determined on the production performance, carcass yield and gastrointestinal morphology from 1-45 days of age. Materials and Methods: A total of 384 ducks were divided into 4 treatments and each treatment consisted of 6 replicates of 16 ducks each. A completely randomized design with a 2×2 factorial pattern was used with 2 main effects: (1) Nutrients levels (D) (conventional diet, CD and low protein and energy diet, LD) and (2) Multi-enzyme supplementation (E) (non-supplemented, NS and supplemented, S). Results: In terms of nutrient levels, reduction of protein and energy in diet (LD) significantly depressed the average body weight (BW, p